O pensamento crítico nas aulas de Física da Universidade Federal de Roraima - Rosa, José Eugênio Brum da (2020)
The research work present here was guided by the scientific problem: does the teaching-learn- ing process developed in the Physics classes at UFRR contribute to the development of critical thinking? Assuming the premise that thinking critically means harmoniously mobilizing a spe- cific set of cognitive skills and based on theoretical parameters established in Historical-cultural and Activity theories, we investigate the development of critical thinking in the context of Phys- ics classes taught at the Federal University of Roraima . From a qualitative approach, we inves- tigate the pedagogical practices of Physics classes from two axes: the pedagogical project of the course and the perspective of the teachers. The data were obtained from documentary re- search and semi-structured interviews. The discussion of the data was based on Textual Discur- sive Analysis and Content Analysis. The analyzes revealed that the pedagogical project of the course meets the determinations of the set of rules that govern national education and advocates critical thinking and its skills as the purposes of the intended training. They also revealed that teachers do not intentionally direct their practices towards the development of critical thinking; however, they do it indirectly. From these results, we defend the thesis that pedagogical prac- tices that characterize the teaching-learning process in UFRR Physics classes contribute to the development of critical thinking, insofar as they contribute to the development of skills related to it, despite there being no explicit intentionality in the actions teachers. Based on the results obtained and the theoretical support of the research, we present a didactic proposal to assist teachers in stimulating the development of critical thinking and their skills.